Characterization the non-covalent interactions between beta lactoglobulin and selected phenolic acids. (August 2020) - Li, Xin; Dai, Taotao; Hu, Peng; Zhang, Chenghao; Chen, Jun; Liu, Chengmei; Li, Ti
Abstract: The interactions between β-lactoglobulin (β-LG) and two types of phenolic acids, including 3, 4-dihydroxybenzoic acid, gallic acid, syringic acid, caffeic acid, ferulic acid, and chlorogenic acid, were investigated by spectroscopy and molecular docking. The fluorescence quenching suggested the formation of a stable phenolic acid-β-LG complex. The thermodynamic parameters suggested that hydrophobic forces dominated the interaction process and the interaction was studied by the molecular docking. The circular dichroism spectra showed the selected phenolic acid induced secondary structure transition of the β-LG from β-sheet to β-turn and α-helix. Interestingly, two types of selected phenolic acids had different effects on the surface hydrophobicity of β-LG. Furthermore, the binding affinity decreased in the order CaA > ChA > FA > SA > DA > GA, which revealed that hydroxylation, methylation, steric hindrance and the type of phenolic acids affected the binding affinity. Cinnamic acid derivatives (CaA, FA, and ChA) exhibited a stronger binding affinity with β-LG than benzoic acid derivatives (DA, GA, and SA). The influence of methylation and the number of hydroxyl groups on the phenolic acids depended on phenolic acid type, the steric hindrance effects reduced their binding ability. The findings obtained herein are helpful to bring out the binding mechanism of phenolic acids and β-lactoglobulin. Graphical abstract: Image 1 Highlights: CAs exhibited a stronger binding affinity with β-LG than BAs. Binding of phenolic acids lead to partial structural destabilization of β-LG. Hydrophobic forces dominated the interaction between phenolic acids and β-LG. Spectroscopy and molecular docking explored the protein-polyphenol interaction mechanism.